Risk-Stratified Cardiovascular Screening Including Angiographic and Procedural Outcomes of Percutaneous Coronary Interventions in Renal Transplant Candidates - Julian König; Martin Möckel; Eda Mueller; Wolfgang Bocksch; Seema Baid-Agrawal; Nina Babel; Ralf Schindler; Petra Reinke; Peter Nickel (Journal of Transplantation)
Background. Benefits of cardiac screening in kidney transplant candidates (KTC) will be dependent on the availability of effective interventions. We retrospectively evaluated characteristics and outcome of percutaneous coronary interventions (PCI) in KTC selected for revascularization by a cardiac screening approach. Methods. In 267 patients evaluated 2003 to 2006, screening tests performed were reviewed and PCI characteristics correlated with major adverse cardiovascular events (MACE) during a follow-up of 55 months. Results. Stress tests in 154 patients showed ischemia in 28 patients (89% high risk). Of 58 patients with coronary angiography, 38 had significant stenoses and 18 cardiac interventions (6.7% of all). 29 coronary lesions in 17/18 patients were treated by PCI. Angiographic success rate was 93.1%, but procedural success rate was only 86.2%. Long lesions (P=0.029) and diffuse disease (P=0.043) were associated with MACE. In high risk patients, cardiac screening did not improve outcome as 21.7% of patients with versus 15.5% of patients without properly performed cardiac screening had MACE (P=0.319). Conclusion. The moderate procedural success of PCI and poor outcome in long and diffuse coronary lesions underscore the need to define appropriate revascularization strategies in KTC, which will be a prerequisite for cardiac screening to improve outcome in these high-risk patients.